Changes in proximate composition, lipid class and fatty acid profile in Greenshell™ mussels (Perna canaliculus) over an annual cycle. (1st December 2017) - Miller, Matthew R; Tian, Hong
Abstract: Greenshell™ mussel (GSM, Perna canaliculus ) is New Zealand's most important aquaculture species. This study looked at changes in the proximate composition, lipid class and fatty acid profile of male and female market ready mussels over a year from April 2016 through to March 2017. There were differences over the season as well as differences between male and female mussels. Winter GSM had lower lipid, carbohydrate and protein concentrations than other seasons. Female mussels had a higher lipid (on average 1.8 ± 0.5 g/100 g ww) and carbohydrate (on average 5.0 ± 1.1 g/100 g ww) compared with the males (lipid, 1.5 ± 0.4 g/100 g ww and carbohydrate 4.5 ± 1.2 g/100 g ww). The major differences observed between seasons in the omega 3 and fatty acids content of the GSM were driven by the fat content, with the highest fat content found in female mussels in the spring prior to spawning. The majority of lipids found in mussels are polar lipids. Overall, this study provides the most comprehensive data on the composition and the lipid content of GSM to date and provides solid base‐line data as the New Zealand GSM industry continues to improve their production procedures. The enhanced nutritional payload of mussels harvested outside of winter (particularly female mussels in spring) could drive a differentiated higher value mussel product.